MINAT SISWA LAKI-LAKI TERHADAP KEGIATAN EKSTRAKURIKULER TARI DI SMA KARTIKA 1-5 PADANG - Nurul Intan Pratiwi; Fuji Astuti; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2018)
AbstractThis article aims to describe the male students ' interest towards extracurricular activities in high school Kartika 1-5 Padang. This research aimed to describe male students’ interest toward extracurricular learning at SMA Kartika 1-5 Padang.This research was qualitative research using descriptive method. The object of this research was male students attending Dance learning. The main instrument was the researcher herself and the additional instruments were stationary, and camera. There were primary and secondary data. The data were collected by using observation, documentation, interview, and library research. The data were analyzing by using several steps: data collection, data reduction, data clarification, and the conclusion.The result showed that the male students’ interest in extracurricular learning was good. It can be seen from several factors: 1) school environment; students used to participate in dance competition, 2) personality; students chose their activity based in hobby and talent they had.Keywords: interest, male students, Extracurricular Dance